The Current Status of Physicochemical Parameters and Water Quality of Sundarijal Reservoir - Dhungana, Ram Prasad (Journal of Science and Engineering, 2019)
Physico-chemical parameters and bacteriological characteristics of water were studied in sample collected from Sundarijal reservoir in January 2018. The present sanitary condition and human activities near the water bodies were also observed. It has been found that the physico-chemical characters were within the standard of World Health Organization (WHO) and National Drinking Water Quality Standards (NDWQS) for drinking water though the public awareness and proper management of watershed and reservoir premises were lacking. However, the coliform bacteria were high and water was not safe to consume without intense treatments with disinfectants.